Crisis management challenges in Kaliningrad - Krasnov, E. V.; Karpenko, Anna; Simons, Greg (Post-Soviet politics, 2014)
This book is an analysis of Britain's war against Al Qaeda and the phenomenon of international terrorism which marked a paradigm shift in the nature and conduct of war in the twenty-first century. At the heart of the book is an attempt to understand why Britain, which possessed a wealth of experience in the conduct of counterterrorism.